(untitled) (International Journal of Engineering and Computer Science, 2014)
In this paper we humbly present an effort in the direction of identifying major diseases in soybean crop, by application of cluster analysis. Data mining in agriculture is in itself a relatively new research field. The use of cluster analysis in the field of agriculture is relatively in its nascent form. A few techniques of cluster analysis have also been discussed here. It includes hierarchical agglomerative clustering approach, fuzzy clustering, hierarchical divisive clustering and Kohonen self-organizing feature maps. This is our strong belief that more effective techniques can be carved out in future for finding the root cause factors for spreading of various diseases in various crops and also for solving different agricultural problems of various complexities and domains, by intelligent use of data mining and its tools such as cluster analysis, classification and prediction